(Trans)formação de professores na era digital. - Santos, Anne Stephanie Severino de Mendonça (Universidade Federal do Tocantins, 2022)
This paper proposes to raise questions about teacher education in the current digital age. The context of the new corona virus pandemic highlighted the importance of thinking and rethinking the pedagogical practices of universities with regard to the preparation of future education professionals to work in the classrooms of today's post-industrial. Students in the digital age are not the same as previous generations and teacher education needs to keep up with changes in society. The research on which this article is based is bibliographic and analytical in nature, with the search for texts, articles and books by authors who speak on the subject. Therefore, we will base our reflections on the postulates of Almeida (1999); Presnsky (2001); Gatti (2010); Kennski (2015-2019); among other authors. The study indicated that, despite recognizing the need for ICT in the classroom, little progress has been made in creating public policies that guarantee the necessary preparation of teachers working in the classroom to guarantee a truly profitable class with the use of ICT and that university curricula need to focus more on training future teachers to teach students in today's digital age.